Preparation of Au-Ag Bimetals and Large-Size Porous Gold Nanostructured Materials - Xuewen Chen (Advances in Materials Science and Engineering)
Gold, silver, and other precious metals are very important nonferrous metals and have been widely applied in fields such as electronics, medicine, metallurgy, pharmaceuticals, and transportation. Adjustable properties of precious metals are mainly attributed to controlled synthesis of precious metals by structure, size, composition, and morphology. Synthesis of binary metals focuses on coordination of physical and chemical properties of metal elements in components, with the aim to give full play to the advantages of the two metals. Gold (Au) and silver (Ag) have similar lattice constants, which provide important theoretical basis for obtaining the binary bimetallic nanostructure of the two metals by coreduction at room temperature. Ag–Au alloy was prepared at different molar ratios of Ag+/AuIII, and the bimetallic nanomaterials obtained had similar Ag/Au ratios to the molar ratio at reaction. This suggested that the bimetallic nanomaterials reacted completely, with the maximum average size in Ag90.1–Au9.9 and the minimum average size in Ag83.2–Au16.8 and Ag66.9–Au33.1. Due to the deficiency of conventional etching agents, the “regrowth etching” method was proposed in this study. Specifically, with AuI as the etching agent, the porous gold nanomaterials with the size of more than 300 nm were successfully prepared, achieving the regrowth etching effect and a good structural stability. According to the analysis based on the catalytic reduction reaction with p-nitrophenol, the properties of the large-size porous gold nanomaterials were related to the quantity and size of pores.